Impact Of Specific And Macroeconomic Variables On Islamic Stock Price - Aida Bela Silfia; Idah Zuhroh (Jurnal Ilmu Ekonomi, 2022)
This study aims to analyze the effect of fundamental variables and macroeconomic variables on sharia stock prices in the Jakarta Islamic Index (JII) for 1 periode 20116-2020 which publishes financial statements successively. The analytical method used is panel data regression with Common Effect Model (CEM) research model and assisted by the Eviews 9 program. The partial results show that all variables have a significant effect on Sharia Stock Prices except the Earning Per Share (EPS) variable has no effect significant to the Sharia Share Price. While the results of the study simultaneously all variables have a significant influence on the islamic stock price.